Soros Economic Development Fund : rethinking support for a Haiti mango processor - Rae, Douglas (SAGE Knowledge. Cases., 2017)
The Soros Economic Development Fund was used to operating in risky environments. Its mission was to make program-related equity investments in developing countries, and it had built up a sound track record in countries like Bulgaria, Liberia, and India.Haiti was another place where SEDF was investing, and since 2003 the organization had been successfully funding a microfinance institution in Port-au-Prince. SEDF had focused on financial services and logistics, but in 2009 it learned about an attractive opportunity in Haiti's agriculture sector.